Abnormal eating attitudes and weight loss behaviours of girls attending a "traditional" Jewish high school in Johannesburg : an examination of teachers' awareness - Notelovitz, Talia (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MNutr)--University of Stellenbosch, 2011.